A fieldable, high-throughput, cost-efficient high performance liquid chromatography-ultraviolet absorption detection (HPLC-UV) method for the quantitation of bispyridinium quaternary aldoxime cholinesterase reactivators in blood - Karvaly, Gellért Balázs; Tekes, Kornélia; Szimrók, Zoltán; FŰrÉsz, József; KuČa, Kamil; Kalász, Huba (Acta chromatographica, 2021)
Mono- and bis-pyridinium quaternary aldoximes (K-oximes) have long been employed as cholinesterase reactivator components of antidotes against lethal cholinesterase-inhibiting organophosphorous chemicals. Their positive charge poses difficulties in their chromatographic analysis, resulting in the publication of different approaches for each K-oxime. A multiplexed method is presented for the rapid quantitation of 10 K-oximes in blood with its utility demonstrated in vivo . Liquid chromatography with absorbance detection was employed. Reversed-phase separation was achieved on a highly nonpolar stationary phase. Method validation was based on the respective guideline of the European Medicines Agency. Times to peak concentrations and 120-min areas under the time–concentration curves were determined in rats following intraperitoneal administration. Adequate retention and separation of K-oximes with acceptable peak shapes in short isocratic runs was achieved by adjusting ionic strength, organic content and the concentration of the ion-pairing agent of the mobile phase. Chromatographic properties were governed by optimizing the concentration of dissolved ions. Accurate adjustment of the organic content was indispensable for avoiding peak drifting and splitting. Dose-adjusted exposure to K-347 and K-868 was exceptionally low, while exposure to K-48 was the highest. The method is suitable for screening systemic exposure to various K-oximes and can be extended.